RELIABILITY OF MODERN RADIOGRAPHIC DENTAL AGE ESTIMATION METHODS AMONG YEMENI CHILDREN IN SANA’A CITY, YEMEN - Abdul-Majid, Arij Lutf Abdulrhman; Aleryani, Husam Abdullah Anas; Aldeen, Yusra Ahmed Ali Sharf; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2025)
Background and aim: Without requiring any more radiographic research, dental age assessment using panoramic X-rays is particularly helpful to children dentists and orthodontists when arranging treatments. The purpose of this study was to evaluate the precision of three contemporary radiography techniques for estimating Yemeni children’s dental ages. Methods: The methods are Demirjian’s method, Cameriere’s open apex method and Al-Qahtani’s London Atlas, in Sana’a City, Yemeni sample. The 1200 radiographs of Yemeni Children (592 girls and 608 boys) aged under the age 18 years were analyzed by the three methods. The accuracy of each method was assessed using the mean difference and t-tests were used to assess the difference between chronological age and dental age within each age category. Results: Demirjian’s method significantly underestimated age for both sexes (p< 0.001), according to the results, with a mean difference of 0.67 years (a mean difference of 0.69 years for boys and 0.66 years for girls). With a mean difference of 0.93 years (a mean difference of 0.92 years for girls and 0.94 years for boys), the Cameriere’s open apex method also significantly underestimated age for both sexes (p<0.001). In contrast, only the 6–6.99 and 7–7.99 age groups showed no significant differences between chronological age and dental age in either method or gender. Conclusion: When it came to determining dental age, the London Atlas approach was the most accurate, followed by Demirjian’s method, and the Cameriere’s method was the least accurate. Furthermore, all three techniques were determined to be trustworthy and could be helpful in determining the age of Yemeni children whose chronological ages are unknown. For every age group, more research with a larger sample is needed. Peer Review History: Received 21 October 2024; Reviewed 13 November; Accepted 18 December; Available online 15 January 2025 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewers: Dr. Rana Ahmed MohamedEl-Saied El-Fitiany, Ahram Canadian University, Giza, Egypt, marmarelfitiany@gmail.com Dr. Rawaa Souhil Al-Kayali, Aleppo University, Syria, rawah67@hotmail.com